RELIGIOUSITY IN THE STORY â€œA DEER THAT ALWAYS REMEMBERS GODâ€: FABLE FROM SUNDA LAND - Atisah, Atisah (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2021)
This paper aims to analyze and reveal the values of religiosity in the animal story or fable "A Mouse Deer Who Always Remembers God". The method used is descriptive analysis method and the theory used to analyze the work is an objective theory based on the work itself. In the fable, the deer figure is very famous, he is smart and always gets a solution when facing problems. He often uses his senses well. In the story "A Mouse Deer Who Always Remembers God", the deer figure always gets a solution to every problem because he always remembers God. The author of the (anonymous) deer story seems to realize that even a creature (animal) always remembers God, what about us humans? By always remembering God life will be saved. This is the hidden message of the author. This fable genre turns out not only to function as entertainment, it also has various functions such as didactic functions, advice, satire, and even.AbstrakTulisan ini bertujuan untuk menganalisis dan mengungkapkan nilai-nilai religiusitas dalam cerita binatang atau fabel â€œSeekor Kancil yang Selalu Ingat Kepada Tuhanâ€. Metode yang digunakan adalah metode deskriptif analisis dan teori yang digunakan untuk menganalisis karya adalah teori objektif yang bertumpu pada karya itu sendiri.Â  Dalam fabel sosok kancil sangat terkenal, ia berwatak cerdik dan selalu mendapat solusi ketika menghadapi masalah. Ia sering menggunakan akal dengan baik. Pada cerita â€œSeekor Kancil yang Selalu Ingat Pada Tuhanâ€, sosok kancil selalu mendapat solusiÂ  dari setiap masalah karena ia selalu ingat pada Tuhan. Pengarang cerita kancil (anonim) tersebut tampak menyadari, bahwa seekor makhluk (binatang) pun selalu ingat Tuhan, bagaiman dengan kita seorang manusia? Dengan selalu mengingat Tuhan hidup akan selamat. Inilah pesan tersembunyi pengarang.Genre fabel ini ternyata tidak hanya berfungsi sebagai hiburan, juga memiliki berbagaiÂ  fungsi seperti fungsi didaktik, nasihat, sindiran, bahkan kritik sosial.Â